Transcriptional responses of liver and spleen in Lota lota to polyriboinosinic polyribocytidylic acid - Lou, Fangrui; Zhang, Yuan; Xu, Anle; Gao, Tianxiang (Frontiers in Immunology, 2023)
The cultured Lota lota can meet the market demand in the context of the decline of wild resources, but the disease in the high-density culture process also deserves attention. Therefore, understanding the immune regulation mechanisms of L. lota will be the basis for obtaining high benefits in artificial culture. To explore the viral response mechanism of L. lota, RNA-seq was applied to identify the transcriptomic changes of the liver and spleen in L. lota by poly (I:C) stress. Results showed that the DEGs (liver: 2186 to 3123; spleen 1542 to 2622) and up-regulated genes (liver: 1231 to 1776; spleen 769 to 1502) in the liver and spleen increased with the prolongation (12h to 48h) of poly (I:C)-stimulation time. This means L. lota needs to mobilize more functional genes in response to longer periods of poly (I:C)-stimulation. Despite the responses of L. lota to poly (I:C) showed tissue-specificity, we hypothesized that both liver and spleen of L. lota can respond to poly (I:C) challenge may be through promoting apoptosis of DNA-damaged cells, increasing the activity of immune-enhancing enzymes, and increasing energy supply based on DEGs annotation information. Our results demonstrate the transcriptional responses of L. lota to poly (I:C)-stimulation, and these data provide the first resource on the genetic regulation mechanisms of L. lota against viruses. Furthermore, the present study can provide basic information for the prevention of viral diseases in L. lota artificial culture process.